Bleeding iliac artery pseudoaneurysm after colorectal anastomotic leak. Issue 4 (November 2016) - Sammour, Tarik; An, Vinna; Thomas, Michelle L.
Abstract : Penetrating and blunt trauma, infection and dissection are all reported causes of abdominal pseudoaneurysms, which are usually managed by endovascular embolization. We report the first case in the literature of a pelvic pseudoaneurysm secondary to a colorectal anastomotic leak.